Analytical and computational modelling for wave energy systems：the example of oscillating wave surge converters - Dias, Frédéric; Renzi, Emiliano; Gallagher, Sarah; Sarkar, Dripta; Wei, Yanji; Abadie, Thomas; Cummins, Cathal; Rafiee, Ashkan (Acta mechanica Sinica, 2017)
The development of new wave energy converters has shed light on a number of unanswered questions in fluid mechanics, but has also identified a number of new issues of importance for their future deployment. The main concerns relevant to the practical use of wave energy converters are sustainability, survivability, and maintainability. Of course,it is also necessary to maximize the capture per unit area of the structure as well as to minimize the cost. In this review, we consider some of the questions related to the topics of sustainability, survivability, and maintenance access, with respect to sea conditions, for generic wave energy converters with an emphasis on the oscillating wave surge converter. New analytical models that have been developed are a topic of particular discussion. It is also shown how existing numerical models have been pushed to their limits to provide answers to open questions relating to the operation and characteristics of wave energy converters.